Effectiveness of Nurse-Led mHealth on Self-Efficacy and Adherence Hemodialysis Patients: A Systematic Review - I Made Dwi Budhiasa Ari Serengga; Ika Yuni Widyawati; Iqlima Dwi Kurnia (Universitas Pahlawan Tuanku Tambusai, 2026)
ABSTRACT Introduction:. Hemodialysis patients with end-stage renal disease (ESRD) often experience low self-efficacy and poor adherence to treatment regimens, which negatively affect their health outcomes and quality of life. Conventional education methods have shown limited effectiveness in sustaining behavioral change. Nurse-led mobile health (mHealth) interventions provide an innovative approach that combines nursing expertise, behavioral theory, and digital technology to enhance self-efficacy and long-term adherence. Methods: This systematic review followed the PRISMA 2020 guidelines and included studies published between 2019 and 2025 from four databases: Scopus, PubMed, ProQuest, and Web of Science. Eligible studies examined nurse-led mHealth interventions aimed at improving self-efficacy and adherence among adult hemodialysis patients. The methodological quality of the included studies was evaluated using the JBI critical appraisal tools. Results: Fourteen studies met the inclusion criteria, comprising randomized controlled trials and quasi-experimental designs. Nurse-led mHealth interventions were delivered through mobile applications, telehealth platforms, and instant messaging systems, demonstrating consistent improvements in self-efficacy, adherence, and clinical indicators. Interventions guided by the FITT (Frequency, Intensity, Time, Type) framework and behavioral theories such as the Health Belief Model, Self-Efficacy Theory, and Transtheoretical Model achieved the most sustainable outcomes. Conclusions: Nurse-led mHealth interventions effectively improve self-efficacy and adherence among hemodialysis patients. Integrating behavioral theory, optimized digital dosage, and nursing leadership represents a scalable strategy to strengthen chronic disease management and patient empowerment in contemporary nursing practice. Keywords: Adherence, HBM , Health Education, Self-management, Self-efficacy